Strategiczna karta inwestycyjna - Kozłowski, Waldemar (The Balanced Scoreinvestment, 2007)
This paper presents the results of a study and observations concerning the relationship between real investments and enterprise development strategy. The investment strategy adopted three perspectives of economics, marketing, and people, which determine enterprise strategy. Therefore, while defining investment strategy it is essential to specify important elements of the enterprise strategy. This enables a detailed determination of their specific character which, in turn, affects the applied cost-effectiveness evaluation methodology and, particularly, enterprise risk.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1159, s. 213-220